Terminal Ediacaran microbialite lithofacies associations with paleo-environmental constraints in a high-frequency sequence stratigraphic framework of Sichuan Basin, SW China - Zhou, Yuanquan; Li, Zhong (Frontiers in Earth Science, 2023)
The terminal Ediacaran shallow marine microbialites are significant for paleo-environment reconstruction and petroleum exploration. Their depositional and paleo-environmental characteristics during high-frequency sea-level fluctuations were paid less attention, which limited the understanding of their evolution and related reservoir characterization. Microbialites from the fourth member of the upper Ediacaran Dengying Formation, Gaoshiti-Moxi area, Sichuan Basin, SW China are important records for studying their lithofacies associations and paleo-environmental constraints in high-frequency depositional sequences. Petrographic and geochemical analyses (in-situ major and trace elements and carbon and oxygen isotopes) indicate microbialites depositional and paleo-environmental evolution on a rimmed platform within a fourth-order depositional sequence. From late TST (transgressive systems tract) to early HST (highstand systems tract), thick-bedded dark-grey dolomudstone-thin-bedded spotted thrombolite dominates the platform margin; while thick-bedded dark-grey dolomudstone-thin bedded dark-grey wavy stromatolite dominates the platform interior. From late HST to early TST of the next fourth-order sequence, the platform margin is dominated by thick-bedded spotted thrombolite—dolograinstone, while the carbonate interior is dominated by thin-medium-bedded layered thrombolite—light-grey wavy stromatolite. Salinity correlates well with microbialite lithofacies associations: the platform interior layered thrombolite and wavy stromatolite enriched lithofacies associations are characterized by higher salinity than that of the platform margin spotted thrombolite enriched lithofacies associations. The microbialite lithofacies associations are less constrained by redox: platform interior layered thrombolite and wavy stromatolite enriched lithofacies associations are slightly more reduced than the platform interior spotted thrombolite enriched lithofacies associations. The redox analysis of the microbialites also indicates low oxygen levels of shallow marine in the study area during terminal Ediacaran, with possible oxygenation at the Ediacaran-Cambrian boundary. The study suggests that the terminal Ediacaran microbialite development was controlled by both high-frequency sea-level fluctuations and paleo-environmental factors such as salinity and redox. Platform margin spotted thrombolitic reefs from late fourth-order HST to next early fourth-order TST serve as favorable microbialite reservoirs. Platform interior layered thrombolites and wavy stromatolites are regarded as potential reservoirs, which deserve more detailed depositional-paleo-environmental research.